The organization of Philippine vocal and instrumental scores in selected academic music libraries in Metro Manila a survey - Baradas, Josephine Cecilia Lontoc 1963- (2000)
Majority of the librarians/catalogers have come up with thier own improvised subject headings for Philippine music scores. The subject authority lists, i.e., Sears List and LCSH seem to be insufficient in that the music libraries needed to improvise the subject headings assigned to Philippine music scores and music books. Majority of the libraries have classified their Philippine music collection of scores as Filipiniana mateials. Two (33 percent) libraries used the DDC system while three (50 percent) libraries make use of the LCC scheme. One (17 percent) library make use of an improvised classification scheme.
The purpose of this study was to determine the following : types of format of Philippine vocal and instrumental music scores that are cataloged in six music libraries in Metro Manila, namely: PWU, SIC, SPCM, SSC, UST, and UPCM; levels of bibliographic description utilized for these scores; sufficiency of the subject authority lists for subject heading assignment for Philippine music scores; provision of additional subject headings; and classification systems adopted for these scores. The music scores analyzed were the published and unpublished Philippine vocal and instrumental music scores composed during the early nineteenth century to the present. This study used the descriptive survey method consisting of questionnaires and interviews.
The recommendations put forth are: 1) librarians without music background and who are assigned to music libraries must provide time to attend some of the music classes offered in their respective music departments; 2) an association of librarians/catalogers must be established to prepare the cataloging in publication for all published and unpublished Philippine music compositions; 3) resource sharing is recommended for the libraries that are in need of Philippine music materials; 4) the notes area should be enhanced by additional information such as: type of notation, first line of a vocal composition, duration of the music piece, and range and key signatures of vocal works; 5) for better access to Philippine music compositions, a review, analysis, and compilation of variant subject headings used or the improvised ones, must be made; 6) the form of music composition and subject content of every music score must be reflected in the subject entries; 7) a compilation or an index of Philippine music tunes and themes must be made; and 8) a list of subject headings applicable to Filipino music compositions be established.
The results of the study show that the four types of bound and unbound Philippine music scores are the music textbooks, music albums, music sheets and music manuscripts. Majority of the libraries have cataloged the Philippine music scores found in music textbooks. Five (83 percent) libraries catalog the published Philippine music album while one library (1 percent) (SPCM) has an improvised style of bibliographic description. Three libraries (50 percent) were able to catalog the Philippine music sheets based on AACR2 while one library (1 percent) (SPCM) has utilized another system. Due to numerous acquisitions of music manuscripts, UPCM has substituted an author/title index for the card catalog. PWU has managed to catalog its music manuscripts while in SSC, the music manuscripts remained uncataloged. No manuscripts were found in UST, SIC and SPCM.
Computer print out.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Vita.
Keywords: Cataloging of music -- Philippines -- Manila Metropolitan Area; Music libraries -- Philippines -- Manila Metropolitan Area